Estudio de la Degradación de Sulfametoxazol Mediante el Sistema UV/H2O2/Cl2 y Aproximación a la Determinación de sus Productos de Degradación por UHPLC/MS (2022)
Pharmaceutically active compounds correspond to a type of pollutants that are currently detected with great frequency in the aquatic environment. Antibiotics specifically represent an additional risk by contributing to the emergence of resistant bacteria. In this work, the efficiency of an electrochemically assisted UV/H2O2/Cl2 system in a flow cell with a dimensionally stable anode and a gas diffusion cathode, under UV radiation (light emitting diode) in the degradation of Sulfamethoxazole, is studied. an antibiotic frequently consumed and detected in surface, waste, hospital and irrigation waters. The influence of parameters such as current density on the production of oxidants and the degradation of Sulfamethoxazole was evaluated. The results show a total degradation of the compound after two minutes of treatment with a maximum mineralization of 35% in thirty minutes. Calculations of energy consumption are made, observing a better efficiency with 75mA/cm2 (0.039kWh/L) compared to 150mA/cm2 (0.060kWh/L). Finally, the possible degradation products obtained by UHPLC/ESI-tqMS were followed up, for which their chemical structures and possible oxidation mechanisms with the reactive and electro-generated species in the system are proposed.